The application of the Analysis Hierarch Process to select the industry in the Cooperative Learning program, Faculty of Engineering, Rajamangala university of Technology Lanna Tak - Jewpanya, Parida (Srinakharinwirot University Engineering Journal, 2020)
The industry selection in the Cooperative Learning program is very importance for students. This is because the students are able to learn and practice in the real places. Therefore, the students should select the suitable industry. In this research, the application of the Analysis Hierarch Process to select the industry in the Cooperative Learning program is proposed. This method can help to find the industry that suitable for each student by considering 4 decision factors including, location, work filed, business type and welfare. In this research, 36 students and 30 industries are selected as a sample group. The type of industries are auto mobile industry, electronic industry and engineering material industry. The result of this study is a list of industries that suitable for each student. Moreover, 5.56% of students are neutral satisfied with the result. 41.67% of students are satisfied and 52.78% of students are very satisfied.